An Interpretive Approach to Understanding How Emotions Leads to Approaches in Using Emojis among Bruneian Gen Z - Adriana Jopri; Syahirah Suhaili (Association of Language Teachers in Southeast Asia (ALTSA), 2024)
In digital spaces where non-verbal cues are absent, Emojis have become a prevalent tool to express emotions in online communication. While past studies focused on the role of Emojis, little has been done to explore how emotional states may influence Emoji usage. This study aimed to explore how Emojis are used, how emotions influence their usage, and the extent to which Gen Z in Brunei use Emojis to express emotions in online communication. By utilising purposive sampling to recruit its participants, the data collected were gathered from a two-part stimulated recall (SR) interview with 10 Bruneian Gen Z, focusing on their responses to the scenarios given and their interpretations of Emojis. The study was also guided by Goleman’s (2001) Emotional Intelligence (EI) model and employed a hermeneutic approach to data analysis. Findings of the study revealed six major themes: (1) Perceived role of Emojis in online communication, (2) Perceived importance of Emojis in online communication and self (3) Emotions and Emojis use, (4), Emoji use according to relationship closeness, (5) Emoji use according to context, and (6) Demographic influences on Emoji use. These findings highlighted Emojis' dual roles of not only expressing but also masking emotions. Emotions were also reported to influence individuals’ Emoji use with key elements of the EI model, specifically self-awareness, self-management, and social awareness, emerging as the prominent aspect of EI among individuals. Nevertheless, other factors including relationship closeness, emotional context, age, and gender, were also found to influence Emoji use. Future research could benefit from including a more culturally diverse and broader age range to further understand how cultural and demographic factors can influence Emoji use.